Avaliação da gestão de resíduos da construção civil exercida em Cuiabá e Várzea Grande - Dondo, Marcello Victor Monteiro (2014)
According to National Waste Solid Politic (Law Nº 12.305/2010) and Environmental Council Resolution Nº 307/2002, waste construction generated in buildings, renovations, extensions and repairs construction, including those resulting from the preparation and excavation belongs to generator, transporter, receiver and processor. The proposed is to evaluate the waste construction management works in Cuiabá and Várzea Grande, through qualitative and quantitative terms, as well offer recommendations for improving the waste management enforceable to Mato Grosso cities. According to the object, to evaluate the construction industry, about waste construction, was elected civil engineering construction, coming from public and private sector, located within the cities of Cuiabá and Várzea Grande, modality new ongoing constructions type, from June/2012 to June/2013, concern dwelling sector. Thus, it will be done: studies with questionnaires and surveys of qualitative and quantitative data with public and private official agencies, buildings and also using descriptive statistics. Through the constructions studied and statistics calculation, waste construction estimated in Cuiabá is 1.085.500 Kg daily, versus 609.500 Kg daily in Várzea Grande. Estimates of generating for new constructions in progress, of housing sector, with large volumes, more than 12.000 m², is 130.850 Kg and 72.770 Kg daily, respectively, according to the methodology use, in Cuiaba and Várzea Grande.